Allu tells stories - Pavel Allu; Valentina Dedyk (Alexander King, 2013)
Allu tells several stories. He is very hard of hearing. His flat is very small, measuring about 2-1/2 meters wide and perhaps 5 meters long. Works in Institute for Advanced Teacher Training, Palana. She was born in a yaranga on the tundra.